Prioritization to ensure care in COVID-19 pandemic - Mirella Rebello Bezerra; Maria Júlia Gonçalves de Mello; Jurema Telles de Oliveira Lima; Zilda do Rêgo Cavalcanti; Guacyra Magalhães Pires Bezerra; Laiane Moraes Dias; Priscilla Karen de Oliveira Sá; Rui Nunes (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to develop a flow to ensure care for all people with severe acute respiratory syndrome Coronavirus 2, offering from intensive care to palliative care, in an equitable and fair manner. Methods: the modified Delphi methodology was used to reach consensus on a flow and a prioritization index among specialists, the regional council of medicine, members of the healthcare system and the local judicial sector. Results: the score was incorporated into the flow as the final phase for building the list of patients who will be referred to intensive care, whenever a ventilator is available. Patients with lower scores should have priority access to the ICU. Patients with higher scores should receive palliative care associated with available curative measures. However, curative measures must be proportionate to the severity of the overall clinical situation and the prognosis. Conclusions: this tool could and will prevent patients from being excluded from access to the necessary health care so that their demands are assessed, their suffering is reduced, and their illnesses are cured, when possible.